Potential of The Citizen Science Project (CSP) to Support Biodiversity Learning in Indonesia - Gusti, Utari Akhir; Hidayat, Topik; Sriyati, Siti; Ananda, Gheri Febri (Bioeducation Journal, 2025)
Conservation of biodiversity in Indonesia is very important. This condition is supported by the high diversity owned but very minimal conservation efforts. Collaborative action between local communities and scientists in learning is needed to support conservation through education. Therefore, it is important to analyze the potential of citizen science projects in biodiversity lessons. This study aims to investigate the potential of citizen science projects and the condition of biodiversity learning in schools. This research is classified as descriptive qualitative. The sampling technique used random sampling with data collection using interviews, questionnaire distribution, and literature study. The results obtained show that citizen science projects have great potential in supporting biodiversity learning in Indonesia with local knowledge owned by indigenous peoples. The results are reinforced by data from students and teachers who agree to support citizen science project innovations in conscious, meaningful, and fun learning. This research reveals learning innovations that become alternatives in learning biodiversity in the success of learning outcomes in the form of conservation through education.